The gigantic beard that was evil - Collins, Stephen, 1980- (Picador, 2014)
"On the island of Here, livin's easy. Conduct is orderly. Lawns are neat. Citizens are clean shaven--and Dave is the most fastidious of them all. Dave is bald, but for a single hair. He loves drawing, his desk job, and the Bangles. But on one fateful day, his life is upended...by an unstoppable (yet pretty impressive) beard."--Back cover.